Internalisasi Nilai-Nilai Pendidikan Islam Dalam Transaksi Non Tunai (Virtual Account Dan Fingerprint) TMI Putri Al-Amien Prenduan - Mantan Pitria; Achmad Maulidi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Al-Amien Prenduan Islamic boarding school issued a new breakthrough in an effort to prevent corruption and theft. Everything that is done by the Al-Amien Prenduan Islamic boarding school aims to instill the value of Islamic education to female students. Since 2019, TMI has required all its students to use digital money in buying and selling transactions. Where parents send money not in the form of cash but through (virtual accounts) so that students use fingerprints in buying and selling transactions.In this study, researchers used a descriptive qualitative approach. To find out about the implementation of non-cash transactions in order to increase the internalization of Islamic educational values at the TMI Putri Al-Amien Prenduan Islamic boarding school. Data collection techniques include observation, interviews and documentation.The results of this study are honest attitude, patient attitude, not wasteful, thrifty and mandate is a form of instillation of Islamic educational values in non-cash transactions.as for internal and external support is a supporting factor while the lack of knowledge of student guardians related to the fingerprint system makes student guardians do not limit remittances every month.